Sach - Bhattacharya, Gautam (New Delhi : Vikas Pub. : Distributors, UBS Publishers' Distributors, 2011)
Biography of Sachin Tendulkar, b. 1973, Indian cricketer.
Library has 2 copies.
Includes bibliographical references and index
Keywords: Tendulkar, Sachin, -- 1973-; Cricket players -- India -- Biography